2011
DOI: 10.1111/j.1755-3768.2011.2211.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐mobility group box‐1 and biomarkers of inflammation in the vitreous from patients with proliferative diabetic retinopathy

Abstract: PurposeTo measure levels of high-mobility group box −1 (HMGB1) and soluble receptor for advanced glycation end products (sRAGE) in the vitreous fluid from patients with proliferative diabetic retinopathy (PDR) and to correlate their levels with clinical disease activity and the levels of the inflammatory biomarkers monocyte chemoattractant protein-1 (MCP-1), soluble intercellular adhesion molecule-1 (sICAM-1), interleukin-1β (IL-1β), and granulocyte macrophage colony-stimulating factor (GM-CSF). In addition, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 36 publications
3
78
0
Order By: Relevance
“…expression in the vitreous fluid and preretinal membranes from patients with PDR and its expression correlated with the activity of the disease and the levels of inflammatory biomarkers [20][21][22]. In addition, we demonstrated that HMGB1 expression was upregulated in the retinas of diabetic mice and rats [21,23].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…expression in the vitreous fluid and preretinal membranes from patients with PDR and its expression correlated with the activity of the disease and the levels of inflammatory biomarkers [20][21][22]. In addition, we demonstrated that HMGB1 expression was upregulated in the retinas of diabetic mice and rats [21,23].…”
Section: Discussionmentioning
confidence: 82%
“…In addition, we demonstrated increased levels of HMGB1 in the vitreous samples from patients with PDR and that there were significant positive correlations between the vitreous levels of HMGB1 and the levels of the inflammatory biomarkers [20][21][22]. Furthermore, we demonstrated that diabetes induced significant upregulation of the expression of HMGB1 and RAGE in the retinas of rats and mice and that intravitreal administration of HMGB1 to normal rats induced activation of inflammatory signaling pathways in the retina and increased retinal vascular permeability [21,23].…”
Section: Introductionmentioning
confidence: 99%
“…This leakage can cause diabetic macular edema (DME) [5]. Several studies have shown marked increases of VEGF in vitreous and vitreous compared to plasma concentration in DME and PDR patients [19,[36][37][38][39][40][41][42][43][44][45][46]. Treatments that target VEGF have been proven highly effective in treating DR. VEGF antibodies, which were originally used for cancer treatments, such as bevacizumab and its correlate ranibizumab have been used effectively.…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%
“…It is believed that the sustained high level of blood glucose in diabetes induces acellular capillaries and pericyte ghosts in retinal microvasculature by unknown mechanisms. Development of DR is a multifarious process where proteases, growth factors, cytokines, and chemokines such as monocyte chemoattractant protein-1 (MCP-1), interleukin-8 (IL-8), intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1, stromal cell-derived factor-1α (SDF-1α), cyclooxygenase-2 (COX-2) and prostaglandin E2 production, vascular endothelial growth factor (VEGF), matrix metalloproteinases (MMPs), and connective tissue growth factor are released from retinal cells under hyperglycemia and interact with each other as well as activate several signaling pathways to promote neovascularization and fibrosis in the retina [7][8][9][10][11]. Considerable experimental evidence, generated in both tissue culture and animal models, indicate that in diabetes, retinal cells undergoes accelerated apoptosis and induces acellular capillaries and pericyte ghosts in retinal vasculature by unknown mechanism [12][13][14].…”
mentioning
confidence: 99%